TRANSGRESSÕES DE BELA E SENSIBILIDADES DA FERA | BEAUTY TRANSGRESSIONS AND BEAST SENSITIVITY - Senna, Nádia (Estudos Linguísticos e Literários, 2018)
Resumo: O trabalho revisita a história da Bela e da Fera para entender contextos de atuação e deslocamentos de gênero conforme comparecem na obra original de Madame de Villeneuve (1740), na versão resumida de Madame de Beaumont (1756) e na versão transgressora de Clarice Lispector (1977). Identificamos simbolismos, relações entre o real e o fantasioso, vislumbramos engajamentos e ambiguidades presentes nas narrativas, nas histórias de vida e nas adaptações cinematográficas produzidas pelos estúdios Pathé (2014) e Disney (1991, 2017). A linha de investigação se baseia nos estudos da cultura visual e de gênero, segundo uma abordagem aberta e híbrida, que conecta diferentes contribuições para destacar ousadias e sensibilidades de belas que também são feras. Abstract: The work revisits the history of Beauty and the Beast to understand contexts of action and gender displacements as they appear in the original work of Madame de Villeneuve (1740), the short version of Madame de Beaumont (1756), and the transgressive version of Clarice Lispector (1977). We identify symbolisms, relations between the real and the fantasy; we envisage engagements and ambiguities present in the narratives, life stories and cinematographic adaptations produced by Pathé (2014) and Disney (1991, 2017) studios. The line of research is based on visual culture and gender studies, using a hybrid approach, which connects different contributions to highlight the daring and sensitivities of beautiful women who are also beasts. Keywords: Transgressions; Sensitivity; Women Writers.